ANALISIS PENGARUH FASILITAS DAN AKSESIBILITAS TERHADAP KEPUASAN WISATAWAN DI DESTINASI KAPALO BANDA TARAM KABUPATEN LIMA PULUH KOTA - Fauzan Ibnu Anugrah; Amsah Hendri Doni (BORJUIS: JURNAL OF ECONOMY, 2025)
This research aims to identify and analyze the effects of facilities (X1) on tourist happiness (Y), the effects of accessibility (X2) on tourist happiness (Y) and the effects of facilities (X1), accessibility (X2) simultaneously on tourist happiness (Y) at the Kapalo Banda Taram tourist destination, 50 Kota Regency. The type of research used in this research is quantitative descriptive research with a quantitative approach and a type of field research using a questionnaire and the number of research illustrations is 100 respondents. The research method used to continue this research uses a quantitative research method with a descriptive approach. By using elasticity in this research is free elasticity (facilities and accessibility) to limited elasticity (happiness). The results of this research are through multiple linear regression analysis proving that there is a significant effect on facilities and accessibility at the Kapalo Banda Taram destination, 50 Kota Regency.